Women’s Literature in Emigration in 1950–1990: the Issue of the Canon - Kolevinskienė, Žydronė (Knygotyra, 2020)
The article was inspired by the World Congress of Lithuanian Writers held in Vilnius, in May 2019, during which the literary canon was discussed – not only in Lithuania, but abroad as well: what determines the entry of some books into the school canon, their assessment with literary prizes, various nominations, and why other books remain less noticed by readers and / or literary critics. The theme of this article was further highlighted by the heated debate on the elections of the Book of the Year that took place throughout the autumn (and is still ongoing). Various top five, top ten, top twelve lists, debates over the update of the contents of the curriculum of secondary schools inevitably raise the issue of the literary canon. Therefore, it is considered that perhaps the problem is not what falls or does not fall into the literary canon, but rather how much power society gives to the literary canon itself. The main tasks of the research: to introduce the main theoretical aspects of the literary canon; to discuss the issue of literary canon and women’s creative works; to identify the dominants of the literary canon in the diaspora. The article discusses the issue of the literary canon precisely in women’s literature that was created and is still being created in the diaspora. Research sources: various literary and cultural presses of the Lithuanian diaspora in the US (Aidai (The Echoes), Darbininkas (The Worker), Draugas (The Friend), Gabija, Naujienos (The News) etc.), Literatūros lankai (Literary Folios) (Buenos Aires, 1952-1959), the book by Vladas Kulbokas Lithuanian Literary Criticism in Exile (Rome, 1982). The main reason for this discussion of (non)canonization of women’s literature is that statistically female authors write more on emigration topics. There were more women writers outside Lithuania in the second wave of emigration (DPs); more women than men give a sense to their exile experience even today. The article emphasizes that women’s involvement in public life has never been either simple or natural. Even greater challenges awaited the creating women in 1944, when they moved to the West – Germany, Austria, and from 1949 – to the US, Canada, Australia. Questions are raised as to how and why public attitudes towards the writing, creative woman have changed; how the community of the Lithuanian diaspora, influenced by a new context, new economic and political conditions in the US, thought about new creative challenges, what kind of goals and objectives were set for it. If feminization processes call for rebellion against the dominant (male) canon, if today we are talking about not a single existing canon, but rather about canons, if it is emphasized that the canon is nonetheless a changing thing related with a system of certain time values, then the canon may not exist at all and it cannot exist? The article also actualizes modern migration processes and their reflections in literature (created both in Lithuania and abroad, outside Lithuania; written not only in Lithuanian but also in English) as well, opens new possibilities for reading and interpreting women’s works – and above all – the article dedicated to the World Lithuanian Year, seeks to create a dialogue field that can help deepen the understanding of today’s (e)migration.
Keywords: literary canon; women’s work; the Lithuanian diaspora; Lithuanian literary criticism in exile